Unique Case of Rare Non-Neural Granular Cell Tumor of the Rectus Abdominis Muscle - Petar Ivanov Kiskinov; Anastas Metaxov Palavurov; Angelina Yanakieva Mollova-Kyosebekirova; Kiril Todorov Atliev; Elean Ivanov Zanzov; Vania Nikolaeva Anastasova (Medicina, 2024)
Background and Objectives: Our report contributes a unique case of a non-neural GCT occurring in an unusual location, with its development during pregnancy adding to its rarity. Materials and Methods: Granular cell tumors (GCTs), also known as Abrikossoff’s tumors, are rare neoplasms of Schwann cell origin with predominantly benign behavior. We present a case of a 29-year-old female with a non-neural variant of a GCT discovered incidentally during a cesarean section, situated on the posterior surface of the rectus abdominis muscle. Results: Histologically, the tumor exhibited features consistent with a benign non-neural GCT, confirmed through an immunohistochemical analysis. Despite the atypical presentation and challenging surgical removal due to prior scarring, the patient experienced no postoperative complications and showed no signs of recurrence during follow-up. Conclusions: This case highlights the importance of considering GCTs in differential diagnoses, particularly in unusual anatomical locations, and underscores the favorable prognosis associated with timely surgical intervention.